Chemical and Volatile Composition of Mango Wines Fermented with Different Saccharomyces cerevisiae Yeast Strains - Li, X.; Yu, B.; Curran, P.; Liu, S.-Q. (South African Journal of Enology and Viticulture, 2011)
The aim of this study was to compare the chemical and volatile composition of mango wines fermented with Saccharomyces cerevisiae var. bayanus EC1118, S. cerevisiae var. chevalieri CICC1028 and S. cerevisiae var. cerevisiae MERIT.ferm. Strains EC1118 and MERIT.ferm showed similar growth patterns but strain CICC1028 grew slightly slowly. The ethanol level reached about 8% (v/v) for each mango wine and sugars (glucose, fructose and sucrose) were almost exhausted at the end of fermentation. There were only negligible changes in the concentrations of citric, succinic and tartaric acids, except for malic acid (decreased significantly). Different volatile compounds were produced, which were mainly fatty acids, alcohols and esters. Most volatiles that were present in the juice were consumed to trace amounts. The kinetic changes of volatiles were similar among the three yeasts but the concentrations of some volatiles varied with yeast. Strain MERIT.ferm produced higher amounts of higher alcohols, isoamyl and 2-phenylethyl acetates, whereas strain CICC1028 produced higher amounts of medium-chain fatty acids and ethyl esters of decanoate and dodecanoate. These results suggest that it may be possible to produce mango wines with differential characteristics using different S. cerevisiae strains.